2016
DOI: 10.1186/s12913-016-1487-2
|View full text |Cite
|
Sign up to set email alerts
|

Do informal caregivers for elderly in the community use support measures? A qualitative study in five European countries

Abstract: BackgroundInformal caregivers are essential figures for maintaining frail elderly at home. Providing informal care can affect the informal caregivers’ physical and psychological health and labour market participation capabilities. They need support to prevent caregiver burden. A variety of existing support measures can help the caregiver care for the elderly at home, but with some limitations. The objective of this review was to explore the experiences of informal caregivers caring for elderly in the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 17 publications
0
36
1
13
Order By: Relevance
“…Such knowledge would enable pharmacy staff to offer more extensive carer support, such as signposting carers to external organisations. Other research has demonstrated that carers may not know which services are available to them and that pharmacists can fulfil an important role as information providers and/or care coordinators . Participants emphasised that information on key support organisations such as Carers Australia was underutilised in practice and that they only became aware of these agencies following training in this study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Such knowledge would enable pharmacy staff to offer more extensive carer support, such as signposting carers to external organisations. Other research has demonstrated that carers may not know which services are available to them and that pharmacists can fulfil an important role as information providers and/or care coordinators . Participants emphasised that information on key support organisations such as Carers Australia was underutilised in practice and that they only became aware of these agencies following training in this study.…”
Section: Discussionmentioning
confidence: 92%
“…Other research has demonstrated that carers may not know which services are available to them [27][28][29] and that pharmacists can fulfil an important role as information providers and/ or care coordinators. [30] Participants emphasised that information on key support organisations such as Carers Australia was underutilised in practice and that they only became aware of these agencies following training in this study. There is an opportunity for pharmacy staff to become more engaged with such organisations, for example during National Carers Week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, informal caregivers are also important actors to stimulate mastery in frail, older adults (Holroyd‐Leduc et al, ). Informal caregivers play an essential role in arranging and managing the continuity of care (Willemse et al, ). The complexity of care recipients' needs influences the relationship with their informal caregivers and the care situation varies depending on, amongst others, the degree of autonomy and control care recipients have (Barrett, Hale, & Butler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Completed carer folders were collected for analysis purposes, following which carers were interviewed by telephone about their experience. Exploratory interview questions (Table ) were developed with reference to the literature (McCann & Bamberg, ; Willemse et al, ; Wilson, Kataria, & McNeilly, ) and feedback from the research team (which included a researcher with lived experience as an adult carer) and key stakeholders, such as an advisor from Carers Queensland and a young carer; this diversity broadened the range of carer perspectives. Interviews were undertaken between March and May 2017 by an experienced qualitative researcher (SM); one carer preferred to provide written feedback to questions due to personal time constraints.…”
Section: Methodsmentioning
confidence: 99%